Lymph Node Metastasis in Patients With Endometrioid Endometrial Cancer: Overtreatment Is the Main Issue. Issue 4 (1st May 2017) - Karalok, Alper; Turan, Taner; Basaran, Derman; Turkmen, Osman; Comert Kimyon, Gunsu; Tulunay, Gokhan; Tasci, Tolga
Abstract : Objective: The aim of this study was to evaluate the effectiveness of histological grade, depth of myometrial invasion, and tumor size to identify lymph node metastasis (LNM) in patients with endometrioid endometrial cancer (EC). Methods: A retrospective computerized database search was performed to identify patients who underwent comprehensive surgical staging for EC between January 1993 and December 2015. The inclusion criterion was endometrioid type EC limited to the uterine corpus. The associations between LNM and surgicopathological factors were evaluated by univariate and multivariate analyses. Results: In total, 368 patients were included. Fifty-five patients (14.9%) had LNM. Median tumor sizes were 4.5 cm (range, 0.7–13 cm) and 3.5 cm (range, 0.4–33.5 cm) in patients with and without LNM, respectively ( P = 0.005). No LMN was detected in patients without myometrial invasion, whereas nodal spread was observed in 7.7% of patients with superficial myometrial invasion and in 22.6% of patients with deep myometrial invasion ( P < 0.0001). Lymph node metastasis tended to be more frequent in patients with grade 3 disease compared with those with grade 1 or 2 disease ( P = 0.131). Conclusions: The risk of lymph node involvement was 30%, even in patients with the highest-risk uterine factors, that is, those who had tumors of greater than 2 cm, deep myometrial invasion, and grade 3 disease, indicating that 70% of these patients underwent unnecessary lymphatic dissection. A precise balance must be achieved between the desire to prevent unnecessary lymphadenectomy and the ability to diagnose LNM.